Grain filling leads to backflow of surplus water from the maize grain to the cob and plant via the xylem - Zhang, Gui-Ping; Marasini, Mukti; Li, Wei-Wei; Zhang, Feng-Lu (Frontiers in Plant Science, 2022)
Rapid dehydration of maize grain is one of the main characteristics of cultivar selection for mechanical grain harvest; however, the dominant driving forces and mechanisms of grain dehydration before physiological maturity remain disputable and obscure. This study compared the grain moisture content and dehydration rate of coated treatment (no surface evaporation) and control grains. Meanwhile, the xylem-mobile dye was infused from stalk and cob, respectively, and its movement was observed in cob, ear- stalk and stalk xylem. The development dynamics of husk, grain and cob were combined to speculate the mechanism of grain dehydration. The results showed that, from grain formation to 5-10 days before physiological maturity, the main driving force of grain dehydration of the early and middle-maturity maize cultivars was filling, followed by surface evaporation. In the dye movement experiment, the movement of the stem-infused xylem-mobile dye through the pedicel xylem was observed during but not after the grain formation period. Moreover, the cob-infused xylem-mobile dye moved to the ear- stalk and the stem via the xylem. There was a significantly positive correlation between grain filling rate and dehydration rate from grain formation to physiological maturity. According to these results, we proposed that in the grain dehydration phase driven by filling, the surplus water in the grain flows back to the cob via the pedicel xylem, of which some flowed back to the plant via cob and ear- stalk xylem. This provides a new theoretical basis for selecting and breeding maize cultivars suitable for mechanical grain harvesting.